Constructing the Eastern geopolitical space by historian Hetum of Corycus - Karagyozyan, Gohar L. (Journal of the Belarusian State University. History, 2025)
The first part of the work of the state and political figure of Cilician Armenia, historian Hetum of Corycus «La flor des estoires de la terre d’Orient», written in 1307 by order of Pope Clement V, is considered. It is established that it describes 14 eastern countries, subject to the Mongol Empire or bordering it, and the peoples inhabiting them, in particular their confessional affiliation and ability to fight. It is noted that when selecting historical-geographical and cultural material, Hetum of Corycus was guided by the interests of Western European readers, so his sketch has features of Western European travelogues, such as alternation of factual data with entertaining stories. It is indicated that the first part of the work is imbued with the author’s idea of the necessity of Armenian-Mongol unity and liberation of the Eastern Christian world from the heathen.